2020
DOI: 10.3390/fermentation6040118
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Fermented Kefir as a Functional Feed Additive in Litopenaeus vannamei Farming

Abstract: Litopenaeus vannamei, known as whiteleg shrimp, is susceptible to infection by pathogenic microorganisms such as viruses and bacteria. Therefore, the prevention of infections in this shrimp is important to regulate the outbreaks of pathogenic microorganisms. In this study, we investigated the effects of kefir as a functional feed additive on innate immunity, survival against WSSV (White Spot Syndrome Virus) and productivity of L. vannamei. As a result, the treatment of kefir could upregulate six of seven genes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 21 publications
1
2
0
Order By: Relevance
“…and yeast was not reduced, compared to other concentrations of dipotassium phosphate (Figure 1a-c) [6]. The number of lactic acid bacteria, Bacillus spp and yeast reached its maximum when 2% seed culture of kefir was inoculated, rather than 10% (Figure 1d) [6]. Based on these results, we finally confirmed the optimum concentration of glucose, whey protein and dipotassium phosphate, and the size of inoculum (Table 1)…”
Section: The Optimization Of Culture Conditions For Kefir Fermentationsupporting
confidence: 62%
See 2 more Smart Citations
“…and yeast was not reduced, compared to other concentrations of dipotassium phosphate (Figure 1a-c) [6]. The number of lactic acid bacteria, Bacillus spp and yeast reached its maximum when 2% seed culture of kefir was inoculated, rather than 10% (Figure 1d) [6]. Based on these results, we finally confirmed the optimum concentration of glucose, whey protein and dipotassium phosphate, and the size of inoculum (Table 1)…”
Section: The Optimization Of Culture Conditions For Kefir Fermentationsupporting
confidence: 62%
“…At 0.02% and 0.1% of dipotassium phosphate, the number of lactic acid bacteria, Bacillus spp. and yeast was not reduced, compared to other concentrations of dipotassium phosphate (Figure 1a-c) [6]. The number of lactic acid bacteria, Bacillus spp and yeast reached its maximum when 2% seed culture of kefir was inoculated, rather than 10% (Figure 1d) [6].…”
Section: The Optimization Of Culture Conditions For Kefir Fermentationmentioning
confidence: 92%
See 1 more Smart Citation
“…These components demonstrated that it's feasible to incorporate them as a replacement for protein, lipids, carbohydrates, vitamins and minerals in aquatic animals' meals to reduce feed expenditures without compromising their quality or hindering growth. In addition, the role of natural feed is to enhance digestive enzymes (Sankar et al, 2011;Labrador et al, 2016) and immune stimulation (Chuchird et al, 2017;Choi et al, 2020), ensure water quality (Amrutha & Shyama, 2018; Rosas et al, 2022) and control the pathogenic microbes (Goba et al, 2018), in addition to stimulating growth in fish and shrimp aquaculture. According to FAO (2022), global fruit production reached 800 million tons, with about 35-45% of wastes which can be reprocessed in the animal and aqua-feed sectors due to substantial nutritive content and plenty of useful components, with an attempt to minimize the negative effects on the environment (Rifna et al, 2021).…”
mentioning
confidence: 99%